Petrologic Evolution of Post-collisional Magmas of Spinel-lherzolite Subcontinental Mantle Contaminated by Continental Crust; Palandoken (Erzurum) Volcanic Rocks in the East Anatolia, Turkey - Kurum, S.; Sar, A.; Nas, N. (Geological Soc India, 2023)
The Palandoken volcanics are made up of a thick volcanic sequence consisting dominantly of tuffs and intercalated lava flows in Erzurum-Tekman basin. According to the data obtained from geochemical analyses, the silica contents of the lavas range from 47.44 % (basalt) to 67.68 % (dacite) and Mg# 11-53%. While alkaline (latite and benmoreite) and subalkaline lavas are generally enriched in large ion lithophile elements (LILE) and light rare earth elements (LREE) in conformity with each other, they show significant negative Nb, Ta anomalies and very weak Eu anomaly. There are also examples (N15, N19) in these rocks that differ in their elements behavior. These geochemical characteristics indicate that, starting from the source magma, various differentiation processes like magma mixing and melt effect, occurred. Whereas the Nd (Nd-143/Nd-144(i)) isotope values of the volcanic rocks vary in a narrow range of 0.51281 and 0.51267, Sr isotope (Sr-87/Sr-86(i)) values have a relatively wider range between 0.70362 and 0.70500, and epsilon Nd(t) values (+0.71 to +5.14). Isotope and geochemical data; supports that these volcanics were formed by the partial melting of spinel-lherzolite subcontinental lithospheric mantle-derived magma at different rates, but assimilation of continental crust also played an important role, along with magma mixing and fractional crystallization, which constitute the main differentiation process.Palandoken volcanic rocks have similar geochemical characteristics with the nearby Ilica, Kandilli and YolcatATIN SMALL LETTER Y WITH ACUTE volcanics in general and their properties are compatible with eastern Anatolian magmatism that was formed in a geodynamic setting of post-collisional extension.
Keywords: Metasomatized Lithospheric Mantle; Collision Zone; Quaternary Volcanism; Trace-Element; Calc-Alkaline; Isotopic Geochemistry; Mafic Volcanism; Lake Van; Petrogenesis; Area